BARAMULLA BECKONS: A HEAVEN FOR TRAVELERS IN JAMMU AND KASHMIR - Shabir Ahmad Lone; Nusrat-ul-Islam Itoo; R. Abida Begum; Mohammad Ishaq Lone (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Tourism plays a pivotal role in fostering economic growth by generating revenue, creating employment, and contributing to GDP in many nations. Known for its unparalleled natural beauty, Kashmir is famously referred to as "Heaven on Earth." Within this region, Baramulla district is distinguished by its rich array of attractions, including gurudwaras, temples, monasteries, and shrines. A key highlight is Gulmarg, located at an elevation of 2,730 meters, which serves as a major tourist draw. Originally called Gauri Marg, the name was changed in the 16th century to Gulmarg, meaning "Valley of Flowers." Other notable sites in Baramulla include the Gulmarg Biosphere Reserve, Khilanmarg, Acchabal, Gondola Lift, Tangmarg, Khilanmarg Golf Course, and Parihaspora. The tourism industry in this district holds substantial potential, providing significant economic opportunities for the local population. This analysis focuses on the district’s major tourist attractions, historical sites, and geographical landmarks, highlighting their contribution to regional tourism development.